Efficacy of Ibandronate Loading Dose on Rapid Pain Relief in Patients With Non-Small Cell Lung Cancer and Cancer Induced Bone Pain: The NVALT-9 Trial - Brouns, Anita J. W. M.; Hendriks, Lizza E. L.; van der Noort, Vincent; van de Borne, Ben E. E. M; Schramel, Franz M. N. H.; Groen, Harry J. M.; Biesma, Bonne; Smit, Hans J. M.; Dingemans, Anne-Marie C. (Frontiers in Oncology, 2020)
Introduction: Approximately 80% of non-small cell lung cancer (NSCLC) patients with bone metastases have cancer induced bone pain (CIBP). Methods: The NVALT-9 was an open-label, single arm, phase II, multicenter study. Main inclusion criterion: bone metastasized NSCLC patients with uncontrolled CIBP (brief pain inventory (BPI) ≥ 5 over last 7 days). Patients were treated with six milligram ibandronate intravenously (day 1-3) once a day. Main exclusion criteria: active secondary malignancy, systemic anti-tumor treatment and radiotherapy ≤4 weeks before study start, previous bisphosphonate treatment. Statistics: Simon’s Optimal two-stage design with a 90% power to declare the treatment active if the pain response rate is ≥ 80% and 95% confidence to declare the treatment inactive if the pain response rate is ≤ 60%. If pain response is observed in ≤12 of the first 19 patients further enrollment will be stopped. Primary endpoint: bone pain response, defined as 25% decrease in worst pain score (PSc) over a 3-day period (day 5-7) compared to baseline PSc with maximum of 25% increase in mean analgesic consumption during the same period. Secondary endpoints: BPI score, quality of life, toxicity and World Health Organization Performance Score. Results: Of the 19 enrolled patients in the first stage, 18 were evaluable for response. All completed ibandronate treatment according to protocol. In 4 (22.2%), a bone pain response was observed. According to the stopping rule, further enrollment was halted. Discussion: Ibandronate loading doses lead to insufficient pain relief in NSCLC patients with CIBP.